The Effect of Primary Care Visits on Total Patient Care Cost: Evidence From the Veterans Health Administration - Jian Gao; Eileen Moran; Rachel Grimm; Andrew Toporek; Christopher Ruser (SAGE Publishing, 2022)
Background: Since the 1980s, primary care (PC) in the US has been recognized as the backbone of healthcare providing comprehensive care to complex patients, coordinating care among specialists, and rendering preventive services to contain costs and improve clinical outcomes. However, the effect of PC visits on total patient care cost has been difficult to quantify. Objective: To assess the effect of PC visits on total patient care cost. Methods: This is a retrospective study of over 5 million patients assigned to a PC provider in the Veterans Health Administration (VHA) in each of the 4 fiscal years (FY 2016-2019). The main outcome of interest is total annual patient care cost. We assessed the effect of primary care visits on total patient care cost first by descriptive statistics, and then by multivariate regressions adjusting for severity of illness and other confounders. We conducted in-depth sensitivity analyses to validate the findings. Results: On average, each additional in-person PC visit was associated with a total cost reduction of $721 (per patient per year). The first PC visit was associated with the largest savings, $3976 on average, and a steady diminishing return was observed. Further, the higher the patient risk (severity of illness), the larger the cost reduction: Among the top 10% of high-risk patients, the first PC in-person visit was associated with a reduction of $16 406 (19%). Conclusions: These findings, substantiated by our exhaustive sensitivity analyses, suggest that expanding PC capacity can significantly reduce overall health care costs and improve patient care outcomes given the former is a strong proxy of the latter.